MicroRNA-34a functions as an anti-metastatic microRNA and suppresses angiogenesis in bladder cancer by directly targeting CD44 - Gan Yu; Weimin Yao; Wei Xiao; Heng Li; Hua Xu; Bin Lang (Journal of Experimental & Clinical Cancer Research, 2014)
Abstract Background Metastasis have considered as an important clinical obstacle in the treatment of human cancer including bladder cancer. Post-transcriptional regulation has emerged as robust effectors of metastasis. MiRNAs are involved in cancer development and progression, acting as tumor suppressors or oncogenes. In this study, we focus on it that microRNA-34a functions as an anti-metastatic microRNA and suppress angiogenesis in bladder cancer by directly targeting CD44. Methods The expression of mir-34a was detected by quantitative real-time PCR. Oligonucleotide and lentivirus were used to overexpress miR-34a. Tube formation assay and transwell assay were used to examine the effect on bladder cancer tube formation, migration and invasion in vitro. Animal models were used to examine the effect on metastasis and angiogenesis in vivo. Luciferase assay was carried out to verify the precise target of miR-34a. Results We not only proved that mir-34a was significantly downregulated in bladder cancer tissues and cell lines but also that circulating miR-34a levels are reduced in bladder cancer, and their levels were positively relevance. Gain-of-function experiments investigated that increased mir-34a expression suppressed tube formation and reduced cell migration and invasion. In vivo metastasis, assays also demonstrated that overexpression of mir34a markedly inhibited bladder cancer metastasis. CD31, an endothelial cell–specific marker which stained in T24 tumors to evaluate for blood vessel density, the immunohistochemistry results showed that blood vessel quantification reduced dramatically in the T24 tumors over-expressing mir-34a. Combining with our previous studies and bioinformatics analysis, we expected that CD44 gene was a direct target of mir-34a, siRNA-mediated knockdown of CD44 partially phenocopied mir-34a overexpression suggesting that the pro-apoptotic role of mir-34a may be mediated primarily through CD44 regulation, whereas restoring the expression of CD44 attenuated the function of mir-34a in bladder cancer cells. Additionally, we identified that EMT (epithelial-mesenchymal transition) related proteins could be regulated by mir-34a which indicated that mir-34a could partially reserve EMT. Conclusion Our study defines a major metastasis and angiogenesis suppressive role for mir-34a, a microRNA functions as a tumor suppressor in bladder cancer by directly targeting CD44, which would be helpful as a therapeutic approach to block bladder cancer metastasis.